Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content 1. The extent of Appropriateness of the school environment within Nablus Directorate for development of talented students at Lower Basic Schools from their teachers’ point of view Mrs. Fayha Abd Al-Salam Sholi 2. The reality of human resource training in the Directorate of Education in the Governorate of Al-Wusta in the Sultanate of Oman from the perspective of employees Mr. Mansoor Abdullah Salim Al-Junaibi 3. A proposed scenario for the partnership between Ministry of Education and the third sector in training secondary school teachers on skills the twenty-first century in the light of global experiences Mr. Mashael Abdullah Ayed Al-Qahtani 4. Evaluation of blended learning during Corona pandemic from the point of view of teachers and principals of public schools in Jerusalem governorate Mrs. Iman Ali Obaydieh Inairat, Dr. Kifah Ahmad Barham 5. Visual Thinking as a Predictor of Cognitive curiosity in Early Childhood Stage in Taif Governorate Co-Prof. Khawlah Jamil Al-Ansari, Mrs. Najlaa Attyah Al-Juaid